Meningkatkan Utilisasi KRL Dengan Mengurangi Waktu Perawatan Akhir Di Balai Yasa KRL Depok - Cahyadi, Dedy; Priyanto, Sapto; Ramadhani, Rizky Dwina (Politeknik Perkeretaapian Indonesia Madiun, 2018)
The increase of population in Indonesia especially in Jabodetabe from year to year has increased significantly, as well as the number of private vehicles which from year to year has increased. By not compensating for the increase in road length, then there will be congestion in the next few years. PT. KCJ is here to deal with the problem. By using rail mode transportation, it will reduce the number of vehicles operating on the highway, thereby reducing congestion. To meet the number of travel needs and offset the increase in population in Greater Jakarta, the availability of facilities at PT. KCJ must comply with applicable provisions. By optimizing the time of maintenance of the facilities, it will obtain the availability of adequate facilities. In this analysis,  we use network planning method to determine the optimal maintenance time of suggestion. In optimizing the maintenance time of the facilities there are several things that influence, among others: the needs of employees, the competence of personnel maintenance personnel, and  reduction of existing backlog. At the end of the research will be known the most optimal time to perform the final treatment, so the availability of facilities will be fulfilled with due regard to the reliability of the means.